Analisis Semiotika John Fiske Mengenai Representasi Maskulinitas Perempuan Dalam Film Disney Cruella - Pranaya, Rolla Sancha; Wijaksono, Dimas Satrio (UNIVERSITAS SARI MUTIARA INDONESIA, 2023)
Disney has been known to produce films with female main characters, not only Disney Princesses but also Disney Villains. This study aims to analyze the concept of female masculinity in the female main character of the Disney film Cruella, which we know as one of the Disney Villain characters. This study uses a qualitative research method with a constructivist paradigm, through John Fiske's semiotic analysis which has a level of reality, a level of representation, and a level of ideology. The results of the research through the reality level show that Cruella has masculine traits such as being dominant, aggressive, ambitious, analytical, able to rely on herself, able to protect herself, able to be a leader, able to make decisions at critical times, and dare to take risks for her actions. At the representation level, it is found that the meaning of masculinity in Cruella is also supported by the technique of taking pictures, audio, and characters in several cut scenes. At the ideological level, the film Cruella presents the ideology of third-wave feminism because this wave also voices recognition of masculine women and feminine men. Many women spread the ideology of feminism with the punk band style in this third wave, where this fashion style was also used by Cruella.